ENGLISH LEARNERS’ LANGUAGE USED FOR CHATTING: A SYNTACTIC AND CONVERSATION ANALYSIS - Nanik Retnowati (ENGLISH, 2019)
Describing language is one of the most important tasks in Linguistics. Language description may give valuable contribution to language teaching practice. This paper is concerning with describing learners’ language used for chatting. Chatting is a spoken language which is written. As a natural language it may have its own structure which can be described. From the point of view of syntax, spoken language usually has its own set of grammar patterns which sometimes may be quite different from that in written language. Language used for chatting would likely provide important information moreover if it is done by language learners who are in the process of trying to make sense of the series of knowledge both on language elements and their usage in the real communication. Chatting task with foreigners was applied to the early semester of English learners. Using Syntactical and Conversation Analysis, this study found the characteristics of the natural language used for chatting and some strategies used by the participants to survive the communication. The description gives an important clue to the benefits of chatting activities for the English learners.